Conservation and improvement of Kankrej cattle (Bos indicus): Status vis-Ã -vis strategies - RATHOD, B S; PATEL, M P; CHAUDHARI, A B; GAMI, Y M; PANCHASARA, H H (The Indian Journal of Animal Sciences, 2021)
The present study was conducted at Livestock Research Station, to compare performance of Kankrej cattle at farm and field condition, and to suggest strategies for the overall improvement of this prestigious breed. The average lactation yield (lit.), standard lactation (lit.), fat percentage, age at first calving and calving interval in the farmers herd was 1669.96±12.24 (1523), 1751.23±12.94 (617), 4.13±0.03 (617), 1464.08±18.41 (260) and 549.93±8.61 (387), respectively during the initial phage of progeny testing program initiated by station and the performance of migratory herd was 2.64 litre (wet average). While, the average lactation yield (lit.), standard lactation (lit.), fat percentage, age at first calving and calving interval at station was 2682.27±126.71 (59), 2501.15±87.72 (59), 4.08±0.09 (49), 1218.42±35.27 (12) and 435.73±13.94 (36), respectively (Elite herd, Anonymous 2018). The lactation yield of daughters born under the progeny testing program was 2050.29±119.20 (104) litres. Looking to the performance gap between the herd maintained at station, field and pastoralist indicates wide scope for the genetic improvement in Kankrej breed by following strict breeding strategies which are discussed in this paper. Conclusively, intensive selective breeding with the use of artificial insemination technology at large scale and progeny testing with precise recording at small scale will solve the purpose in the non-migratory population while, supply of high genetic merit male calf or proven bull’s male calf to the Maldharis having migratory population.